2020
DOI: 10.1038/s41598-020-73741-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin E supplementation on selected inflammatory biomarkers in adults: a systematic review and meta-analysis of randomized clinical trials

Abstract: The previous meta-analysis of clinical trials revealed a beneficial effect of vitamin E supplementation on serum C-reactive protein (CRP) concentrations; however, it is unknown whether this vitamin has the same influence on other inflammatory biomarkers. Also, several clinical trials have been published since the release of earlier meta-analysis. Therefore, we aimed to conduct a comprehensive meta-analysis to summarize current evidence on the effects of vitamin E supplementation on inflammatory biomarkers in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 81 publications
(251 reference statements)
3
44
0
Order By: Relevance
“…Highdose vitamin E is not recommended due to its prooxidant actions. 10 In this study the antiulcerogenic role of vitamin E was assessed against experimentally produced gastric ulcers in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Highdose vitamin E is not recommended due to its prooxidant actions. 10 In this study the antiulcerogenic role of vitamin E was assessed against experimentally produced gastric ulcers in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, comprising eight vitamers (four tocopherols (TFs) and four tocotrienols (TTs)), is the most abundant liposoluble antioxidant compound in the human body, and its modulatory effects regarding signal transduction, cellular pathways (e.g., NF-κB signaling), and gene expression (e.g., pro-inflammatory cytokines) have recently gained notoriety [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though several in vitro and in vivo preclinical studies have reported numerous cellular pathways modulated and beneficial effects exerted by vitamin E, human clinical studies have shown sometimes-conflicting results, skewing towards beneficial and protective action of these molecules; notable differences have been found among them, with some of the 8 vitamers proving to be more efficient than others [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations